Longitudinal imaging of microvascular remodelling in proliferative diabetic retinopathy using adaptive optics scanning light ophthalmoscopy - Chui, Yuen Ping Toco (Ophthalmic Physiol Opt, 2016)
PURPOSE: To characterise longitudinal changes in the retinal microvasculature of type 2 diabetes mellitus (T2DM) as exemplified in a patient with proliferative diabetic retinopathy (PDR) using an adaptive optics scanning light ophthalmoscope (AOSLO). METHODS: A 35 year old T2DM patient with PDR treated with scatter pan-retinal photocoagulation at the inferior retina one day prior to initial AOSLO imaging along with a 24 year old healthy control were imaged in this study. AOSLO vascular structural and perfusion maps were acquired at four visits over a 20 week period. Capillary diameter and microaneurysm area changes were measured on the AOSLO structural maps. Imaging repeatability was established using longitudinal imaging of microvasculature in the healthy control. RESULTS: Capillary occlusion and recanalisation, capillary dilatation, resolution of local retinal haemorrhage, capillary hairpin formation, capillary bend formation, microaneurysm formation, progression and regression were documented over time in a region 2° superior to the fovea in the PDR patient. An identical microvascular network with same capillary diameter was observed in the control subject over time. CONCLUSIONS: High-resolution serial AOSLO imaging enables in vivo observation of vasculopathic changes seen in diabetes mellitus. The implications of this methodology are significant, providing the opportunity for studying the dynamics of the pathological process, as well as the possibility of identifying highly sensitive and non-invasive biomarkers of end organ damage and response to treatment.